Design and implementation of a mobility support adaptive trickle algorithm for RPL in vehicular IoT networks. (27th June 2022) - Kumar, J.N.V.R. Swarup; Suresh, D.
Low-power wireless networks (LPWNs) have been used as single radio transceivers that can use very low TX/RX power to make basic electronics and antennas. But they may end up with asymmetry resulting in insecure and poor wireless communications and further may impact quality of operation. In specific usage with vehicular networks, maintenance of settings with mobility nodes, the operation level is often harder. The proposed method uses RPL as a routing protocol and ensures the factors such as efficient and timely contact with LPWNs under node mobility. In addition, the RPL protocol a Trickle algorithm is introduced to establish routes between nodes at different levels in the network and also to reduce RPL's disadvantages. Also, a RPL metric (MSAT-RPL) is noted as vehicle location timely responds and proposes different strategies in vehicular networks. With the existing models a comparative study was performed in 'Cooja 3.0' simulator platform.